ATTITUDE OF HIGH SCHOOL STUDENTS TOWARDS THE USE OF TECHNOLOGY IN THE EDUCATIONAL PROCESS - DRĂGAN, Lavinia (Revista de pedagogie, 2019)
This paper takes into account the results of a sociological survey based on the opinion poll technique, using a thematic questionnaire. The sample construction (availability sample of a relatively small number of subjects) and the data analysis and interpretation make this research similar to qualitative studies. The questionnaire addresses high school students and it is designed to analyze their perceptions and attitudes about the use of technology in learning and assessment. Both the degree of technology use during individual study and research and the level of capitalization by teachers and pupils during lessons were taken into consideration. The sociological survey also captures the respondents’ opinions on how technology can be used in teaching social science. Taking into account the development of eight key competences established in accordance with the European norms, the way in which digital competencies development can be pursued – besides the general and specific competencies provided by the sociology curriculum – has been investigated. The research results indicate an increased level of students’ receptivity and interest towards the integration of technology in teaching social science, as well as an increase in efficiency regarding teaching aims and objectives. Also, an increase in learners’ intrinsic motivation to study and their willingness to play an active role in the educational process can be observed. In conclusion, integrating technology into the teaching-learning-evaluation process proves to be beneficial, equally meeting the needs of students and teachers.